Analisis Konektivitas Pori pada Sampel Batuan Reservoir Menggunakan Metode Mercury injection capillary pressure (MICP) dan Centrifuge - Sultan Zaki Asiilah; Aici Ichtiarizak Machrifah; Jamaluddin Jamaluddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Pore system characteristics and fluid distribution are important factors affecting reservoir quality, particularly fluid storage and flow capability. This study analyzes capillary pressure characteristics and pore size distribution using Mercury Injection Capillary Pressure (MICP), evaluates the relationship between capillary pressure and fluid saturation distribution using the centrifuge method, and assesses reservoir quality through integration of both methods. The study was conducted on three reservoir rock samples from the Semberah Field, Kutai Basin, namely A1, A2, and A3. Results show that sample A2 had the largest dominant pore throat (5.614 µm), the lowest entry pressure (6 psia), and the lowest Swirr (0.445), indicating good pore connectivity. Sample A3 exhibited the smallest dominant pore throat (0.038 µm), the highest entry pressure (131 psia), and the highest Swirr (0.903), reflecting a tighter pore system. The integration of MICP and centrifuge analyses provides a comprehensive evaluation of pore connectivity, fluid distribution, and reservoir quality.